Pd/SBA-15 catalysts in the catalytic wet air oxidation of phenol (Superficies y Vacío, 2022)
A series of palladium catalysts (0.5, 1.5 and 3.0 wt%) were synthesized by impregnation at pore volume on a silica-based mesoporous molecular sieve (SBA-15). Materials were characterized by N2 physisorption, X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (HR-TEM). The catalytic activity was evaluated in catalytic wet air oxidation (CWAO) of phenol at 160oC, 10 bar, 200 mg of catalyst and 200 mL of phenol from a 500 ppm solution. The results of the characterization show a great influence of the metallic content of Pd; the specific area decreases when introducing a higher percentage of palladium. The materials presented texture, structure and morphology according to what has been observed in literature. It was found that the size of the supported palladium oxide species formed during the calcination stage was smaller in the catalyst with lower metal content (Pd0.5/SBA-15) and this was the most active in the degradation of phenol and degraded 64% of phenol, being the most active of the catalysts.